Afterword: The Work of Diagrams. Issue 4 (1st December 2019) - Engelmann, Lukas; Humphrey, Caroline; Lynteris, Christos
Abstract : Philip Steadman's epilogue suggests that the copying of drawings (and its study) by anthropologists, psychologists, architectural students, and Surrealists is revealing not only of processes of diagrammatization but also of the fact that there is something 'diagrammatic' about the way in which designs are represented mentally, which affects how they are seen and altered when they are reproduced. The work of diagrams, not only as visual objects but also as mental processes, is shown by the articles in this special issue to play a central role in fields as diverse as psychoanalysis, anthropology, epidemiology, and biology. More often than not, the synergy between these fields is facilitated, and sometimes catalyzed, by shared diagrammatic practices. As the studies examined in the epilogue demonstrate, diagrams form a privileged visual field of interdisciplinary dialogue and exchange. But importantly, they also facilitate a way of information processing—what the editors of this special issue call 'diagrammatic reasoning'—through which data are processed, presented, and reconfigured in clear and easily assimilated forms.